Investigation of the Factors Affecting the Removal of an Acid Dye from Aqueous Solution by Adsorption Using Bentonite and Sepiolite - Ceyda Bilgiç (Adsorption Science & Technology)
The effects of some factors on the adsorption of an Acid dye (Acid Blue 193, AB 193) from aqueous solution onto bentonite and sepiolite samples were studied. These factors were saturation of the samples with cations (Na + and Ca 2+ ), the pH and the ionic strength of the dye solution. The Langmuir and Freundlich adsorption models were used to describe the equilibrium isotherm and determine the isotherm constants for each of the samples. The Langmuir model agreed very well with the experimental data. Cation saturation led to an increase in the adsorption capacities of the samples. In addition, the adsorption capacities decreased with increasing pH of the dye solution and increased with increasing ionic strength. The maximum adsorption capacity of both the bentonite and sepiolite samples towards the cationic dye Methylene Blue (MB) was higher than that towards the anionic dye AB 193.